Incidence and Contributing Factors of Persistent Hyperglycemia at 6–12 Weeks Postpartum in Iranian Women with Gestational Diabetes: Results from LAGA Cohort Study - Sedigheh Nouhjah; Hajieh Shahbazian; Nahid Shahbazian; Alireza Jahanshahi; Shayesteh Jahanfar; Bahman Cheraghian (Journal of Diabetes Research)
Background. A history of gestational diabetes is an important predictor of many metabolic disturbances later in life. Method. Life after gestational diabetes Ahvaz Study (LAGAs) is an ongoing population-based cohort study. Up to February 2016, 176 women with gestational diabetes underwent a 75 g oral glucose tolerance test (OGTT) at 6–12 weeks postpartum in Ahvaz (southwestern of Iran). Gestational diabetes was diagnosed according to the International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria and the American Diabetes Association (ADA) criteria applied for diagnosis of postpartum prediabetes and diabetes. Univariate and multivariate regression analysis were done. Results. Overall incidence of early postpartum glucose intolerance was 22.2% (95% CI, 16.3–29.0), 17.6% prediabetes (95% CI, 12.3–24.1) and 4.5% diabetes (95% CI, 2.0–8.8%). Independent risk factors for glucose intolerance were FPG ≥ 100 at the time of OGTT (OR 3.86; 95% CI; 1.60–9.32), earlier diagnosis of GDM (OR 0.92; 95% CI; 0.88–0.97), systolic blood pressure (OR 1.02; 95% CI; 1.002–1.04), and insulin or metformin therapy (OR 3.14; 95% CI; 1.20–8.21). Conclusion. Results determined a relatively high rate of glucose intolerance at 6–12 weeks after GDM pregnancy. Early postpartum screening of type 2 diabetes is needed particularly in women at high risk of type 2 diabetes.